Intratumoral expression of IL-12 and CD40 ligand (CD154) from plasmids generates antitumor responses that eliminate tumoral T regs - Gregory W. Ho; Alicia Santos; Jennifer Fields; Pamela C. Rosato; Mary Jo Turk; Nicole F. Steinmetz; Steven Fiering (Scientific Reports)
Abstract Intratumoral immunotherapy (ITIT) strives to generate effective antitumor immunity by directly stimulating the immune system in tumors to reverse local tumor-mediated immune suppression. In vivo expression of Interleukin-12 (IL-12) using in vivo plasmid transfection as an intratumoral cancer immunotherapy entered Phase II clinical trials for metastatic melanoma but to limited clinical success. We sought to improve the efficacy of in vivo IL-12 electroporation by the addition of a CD154 (CD40 ligand)- expressing plasmid to the IL-12 encoding plasmid treatment and assessing efficacy against solid tumors. Mice with intradermal B16F10 melanoma or MC38 murine colon carcinoma tumors received 2 weekly intratumoral (IT) injections of plasmids encoding IL-12 and CD154, followed by in vivo electroporation. The addition of CD154 to IL-12 was superior to IL-12 alone and resulted in frequent tumor clearance of treated tumors, marked by an increase in CD8 T cells and a drastic reduction in T regulatory cells in the tumor microenvironment. Tumor treatment responses were abrogated in mice which lack conventional DC1 cells (BatF3 KO) or lack CD8 T cells. These findings highlight the potential of adding CD154 to IL-12 plasmid electroporation as a cancer immunotherapy and suggest that other combinations would be therapeutically valuable.